ANALISIS MOTIVASI, PELATIHAN KERJA DAN DISIPLIN KERJA TERHADAP PENINGKATAN KINERJA KARYAWAN PADA DINAS PENDIDIKAN KOTA KEDIRI - Syahru Munir (SINDA: Comprehensive Journal of Islamic Social Studies, 2022)
The results showed that the partial (t test) showed that the motivation variable had no significant effect on the performance of the employees of the Kediri City Education Office, so it can be concluded that H1 was rejected, which means that there was no partial significant effect between the motivational variables on the performance of the employees of the Kediri City Education Office. Partially (t test) shows that the job training variable has a significant effect on the performance of the employees of the Kediri City Education Office, so it can be concluded that H1 is accepted which means that there is a partially significant effect between the job training variables on the performance of the employees of the Kediri City Education Office. The work discipline variable has a significant effect on the performance of the employees of the Kediri City Education Office, so it can be concluded that H1 is accepted, which means that there is a partially significant influence between the work discipline variables on the performance of the employees of the Kediri City Education Office. Based on the F (simultaneous) test, it can be concluded that the variables of motivation, job training and work discipline simultaneously have a significant positive effect on the performance of the employees of the Kediri City Education Office.